One health ethics: "What then must we do?"* - Joann M. Lindenmayer; Gretchen E. Kaufman; Liv Baker; Simon Coghlan; Fred W. Koontz; Joachim Nieuwland; Kristin L. Stewart; William S. Lynn (CABI, 2022)
Abstract One Health, as proclaimed by the United Nations Quadripartite, is "an integrated, unifying approach that aims to sustainably balance and optimize the health of people, animals, and ecosystems." As such, it recognizes that the health of people, other animals, and nature is closely linked and interdependent. A great deal of One Health education, research, and practice is grounded in science, while ethical considerations are addressed infrequently. Yet ethical issues are inherent to each stage of One Health. They include which aspects of interdependencies to study, how to extend health and well-being beyond humans, and what trade-offs to consider when optimizing the health of people, other animals, and nature. In this article, we call for an active debate on the ethical considerations that should underpin every stage of One Health. We propose four tenets for discussion that, if adopted, could serve as springboards from which to consider how we "ought" to teach, investigate, and practice One Health. One Health Impact Statement While science helps us to better understand and explain how humanity's actions affect our planet, ethics helps us evaluate those actions-past, present, and future. Working toward engaging with questions of ethics in conferences and peer-reviewed publications will help to establish guidelines for the conceptualization, design, implementation, and evaluation of One Health teaching, research, policy, and practice. Integrating ethical considerations and debate into every aspect of One Health will support a multispecies understanding of the term "One Health" and move us forward by building a common point of departure for dialogue, deliberation, and decisions inherent in One Health.